Production of Artemia Biomass in Indoor Culture Tank in Bangladesh - Islam, M. S.; Kibria, M. M.; Bhuyan, S. (Journal of Scientific Research, 2019)
Artemia known as brine shrimp that rich in essential amino acids. An excellent food for newly hatched fish and shrimp larvae gained a unique position in the aquaculture system and is given as live feed. The study was carried out to develop an easiest and cheapest technology for the production of Artemia biomass and cyst in the coastal area. Crude salt collected from the salt pan was used to biomass culture of Artemia species. Agricultural by-products (e.g. rice bran, oil-cake, and cod liver oil) were used as food. Adult Artemia sp. was harvested at the age of 15 days after the inoculation of cyst in a hatching tank. From hatching tank, newly hatched nauplii were transferred to larval rearing tank. 63.06 gm (wet weight) of Artemia sp. were collected from each tank and the weight of each Artemia was found 0.0036 g. At the end of the experiment, the survival rate was found 46.12% based on first observation. A sharp growth rate of Artemia sp. was observed on day 11 and it was continued to day 13. At day 14 and onwards the growth of Artemia sp. became almost uniform.